(untitled) (Olhar de Professor, 2025)
This article presents an analysis of my master’s research in Education on the interbody relationships between babies, young children, artists and scenic material, focusing on the experiences of Cia Zin, from São Paulo, in the play Linhas. Inspired by phenomenology and based on childhood studies at the interface with theater, the research questions how it can be done for and with babies, recognizing them as co-creators who challenge traditional conceptions of theater, observing their forms of language and corporeity in performance games, creating different public and shared experiences that transform the meaning of the role of spectator and promote broader understandings of Art, Education and childhood.